Inter-genomic DNA Exchanges and Homeologous Gene Silencing Shaped the Nascent Allopolyploid Coffee Genome (Coffea arabica L.). Issue 9 (1st September 2016) - Lashermes, Philippe; Hueber, Yann; Combes, Marie-Christine; Severac, Dany; Dereeper, Alexis
Abstract: Allopolyploidization is a biological process that has played a major role in plant speciation and evolution. Genomic changes are common consequences of polyploidization, but their dynamics over time are still poorly understood. Coffea arabica, a recently formed allotetraploid, was chosen to study genetic changes that accompany allopolyploid formation. Both RNA-seq and DNA-seq data were generated from two genetically distant C. arabica accessions. Genomic structural variation was investigated using C. canephora, one of its diploid progenitors, as reference genome. The fate of 9047 duplicate homeologous genes was inferred and compared between the accessions. The pattern of SNP density along the reference genome was consistent with the allopolyploid structure. Large genomic duplications or deletions were not detected. Two homeologous copies were retained and expressed in 96% of the genes analyzed. Nevertheless, duplicated genes were found to be affected by various genomic changes leading to homeolog loss or silencing. Genetic and epigenetic changes were evidenced that could have played a major role in the stabilization of the unique ancestral allotetraploid and its subsequent diversification. While the early evolution of C. arabica mainly involved homeologous crossover exchanges, the later stage appears to have relied on more gradual evolution involving gene conversion and homeolog silencing.